PHARMACOGNOSTICAL EVALUATION, IN VITRO ANTIOXIDANT EFFECTS OF SYZYGIUM CUMINI LINN. SEED EXTRACT, AND THE POTENTIAL ROLE OF THIS EXTRACT AS HYPOGLYCEMIC AGENT IN ALLOXANâ€“INDUCED DIABETIC RATS - Biswas, Ranu; Sen, Kalyan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Diabetes, the third killerâ€ of mankind, is now a global burden affecting nearly 10% of the population. The present study aimed at pharmacognostical evaluation of Syzygium cumini seed powder, phytochemical profiling, total phenolic, and flavonoid content determination and to ascertain its antioxidant activity and hypoglycemic potential in alloxan-induced diabetic rats. Methods: Pharmacognostical and physicochemical parameters of the seed powder were determined by using standard methods as per Ayurvedic Pharmacopoeia of India (API). In vitro antioxidant activity was determined by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity. Ethanolic extract of Syzygium cumini seed at a dose of 200mg/kg and 400mg/kg body weight (bw) were given orally in alloxan-induced (150mg/kg, i.p) diabetic rats daily for three weeks. Results: physicochemical parameters complied with the API standards. Phytochemical profiling revealed that the extract contains phenolic compounds, flavonoids, glycosides, alkaloids, tannins, and saponins. The extract is rich in phenolic compounds which were 177.33 mg gallic acid equivalent/g (GAE/g dry weight) and showed significant percentage inhibition compared to standard ascorbic acid. The extract reduced the fasting blood sugar (FBS) level by 46.67â€“52.67% which is very close to the standard drug glibenclamide (reduced FBS by 65.58%). It also improved the bw by 18.20â€“20.41% after extract treatment where the standard drug increased the bw by 22.95% of the diabetic rats. Conclusion: In conclusion, Syzygium cumini seed extract is rich in phenolic compounds. Results suggested that the extract possesses significant radical (DPPH) scavenging activity and FBS lowering potential in alloxan-induced diabetic rats.